Rehabilitation interventions for depression symptoms among cancer patients in Palestine: A systematic review - Battat, Maher Mohammad Khalil; Marie, Mohammad (Frontiers in Rehabilitation Sciences, 2022)
Background Depression enhances disease burden in cancer patients, psychological interventions and rehabilitation of depression are required as a part of palliative care for cancer patients to improve the quality of life and mental health The aim of the study to review the literature about depression treatments and rehabilitation interventions among cancer patients in Palestine Method: Review articles used electronic databases PubMed, Science Direct, Research Gate and Google Scholar to search for materials for the literature review study. Results: twenty three articles reviewed five of them from Arab and Islamic countries, and five articles from Palestine. Overall depression rehabilitation interventions for cancer patients are defined on two themes includes pharmacological interventions, and non-pharmacological interventions used that reduce depression symptoms and improve mental health among cancer patients. Depression rehabilitation interventions among cancer patients in Palestine are limited to palliative care perspective includes psychosocial support, cancer patient symptoms management, and family education. Conclusion: Depression symptoms treatments and rehabilitation interventions in Palestine are limited to non-pharmacological interventions from the perspective of palliative care for cancer patients including psychosocial interventions, besides cancer patient’s symptoms management affects mental health positively and depression recovery. Palliative care including depression symptoms rehabilitations in Palestine needs improvement. Israeli occupation is the main cause of limited rehabilitation and treatment interventions for Palestinian cancer patients. Key Words: Rehabilitation, Mental Health, Treatment, Intervention, Cancer Patients, Depression, Palliative Care, Palestine, West Bank, Gaza Strip.